Importance of oceanographical background for a conservation priority areas network planned using MARXAN decision support tool in the Russian Arctic seas. (September 2017) - Spiridonov, Vassily; Solovyev, Boris; Chuprina, Ekaterina; Pantyulin, Anatoly; Sazonov, Alexei; Nedospasov, Andrei; Stepanova, Svetlana; Belikov, Stanislav; Chernova, Natalia; Gavrilo, Maria; Glazov, Dmitry; Krasnov, Yury; et al.
Abstract: The aim of the present study is to assess a conservation priority area (CPA) network proposed for the Russian Arctic seas (47 areas) with regard to underlying oceanographical features and to discuss further development of marine conservation planning. The oceanographical features included in the analysis were obtained from the literature or inferred from schemes of climatic oceanography. The most frequent oceanographic feature associated with a particular CPA is constant advection of a particular water mass, followed by local water mass transformation, seasonal ice zones, flaw polynyas, and external sources of nutrients. Particularly important are major frontal zones, and coastal phenomena such as coastal/offshore waters transition zones, massifs of fast ice and specific regimes of semi‐isolated fjords and bays. Each Arctic sea in the study area or its large part (in the Barents Sea) is characterized by a distinct combination of oceanographical features associated with the respective CPAs. Although most oceanographical features were not involved in the process of developing the CPA network directly, the resulting CPAs are shown to have a solid oceanographical background. While this oceanographical background needs further understanding, it provides the possibility to refine the MPA boundaries and plan future studies. Furthermore it allows evaluation of potential resistance and resilience of CPAs to climate change by focusing on relevant oceanographical processes and the adaptive potential of biota on an area by area basis.